NVP-BEZ235 Inhibits Renal Cell Carcinoma by Targeting TAK1 and PI3K/Akt/mTOR Pathways - Li, Bihui; Zhang, Xing; Ren, Qianyao; Gao, Li; Tian, Jing (Frontiers in Pharmacology, 2022)
In spite of the promising in vitro and preclinical results, dual PI3K/Akt/mTOR inhibitor NVP-BEZ235, and ATP-competitive mTOR inhibitor PP242 both failed to confirm their inhibitory efficacy against renal cell carcinoma (RCC) in clinical settings. Therefore, a better understanding of the molecular mechanism is essential so as to provide possibilities for their use in combination with other agents. In present study, RCC cell lines (UMRC6, 786-0 and UOK121) were treated with NVP-BEZ235, PP242 or Rapamycin, an mTOR complex 1 (mTORC1)-specific inhibitor. They all suppressed cell proliferation and invasion, induced apoptosis and cell cycle arrest, and the effects were in the order of NVP-BEZ235 > PP242 > Rapamycin. Accordingly, the marked and sustained decrease in speckle-type POZ protein (SPOP) expression and phosphorylation of Akt and mTOR kinases was observed in RCC cells treated with NVP-BEZ235 and PP242, whereas only potent inhibition of mTOR activity was induced in Rapamycin-treated cells. In considering the overactivation of c-Jun and IκB-α in human renal tumor tissue, we next investigated the role of JNK and IKK pathways in the response of RCC cells to these compounds. First of all, transforming growth factor β activated kinase 1 (TAK1)-dependent activation of JNK/ (activator protein-1) AP-1 axis in RCC cells was proved by the repression of AP-1 activity with TAK1 or JNK inhibitor. Second, the profound inhibition of TAK1/JNK/AP-1 pathway was demonstrated in RCC cells treated with NVP-BEZ235 or PP242 but not Rapamycin, which is manifested as a reduction in activity of TAK1, c-Jun and AP-1. Meanwhile, subsequent to TAK1 inactivation, the activation of IκB-α was also reduced by NVP-BEZ235 and PP242. Likewise, in vivo, treatment with NVP-BEZ235 and PP242 suppressed the growth of xenografts generated from 786-0 and A498 cells, along with decreased expression of phospho-TAK1, phospho-c-Jun, and phospho-IκB-α. In contrast, Rapamycin elicited no significant inhibitory effects on tumor growth and phosphorylation of TAK1, c-Jun and IκB-α. We conclude that besides PI3K/Akt/mTOR signaling, NVP-BEZ235, and PP242 simultaneously target TAK1-dependent pathways in RCC cells. Notably, these effects were more marked in the presence of NVP-BEZ235 than PP242, indicating the potential application of NVP-BEZ235 in combination therapy for RCC.